Supporting literacy development in secondary education: identifying and addressing student needs : a curriculum program to assist secondary educators - Schrick, Ann M. (My University, 2025)
This curriculum program is designed to help secondary teachers better support students who struggle with foundational literacy skills. It addresses a significant gap in secondary education, where many students face ongoing literacy challenges despite improvements in elementary reading instruction. The program provides teachers with practical, research-based tools and strategies for identifying and addressing reading difficulties through a Multi-Tiered Support Systems (MTSS) framework. Drawing from cognitive science and the Science of Reading, the program explains how the brain learns to read and offers evidence-based teaching methods, including structured literacy approaches. The content is delivered through an interactive online platform that includes assessment tools, lesson plans, and resources for differentiated instruction. The program emphasizes five key components of literacy: phonemic awareness, phonics, fluency, vocabulary, and comprehension, while incorporating both Scarborough's Reading Rope and Sedita's Writing Rope frameworks. This practical resource aims to empower secondary educators with the knowledge and tools they need to help struggling readers succeed, without requiring extensive additional training or resources.
Keywords: Literacy development; Secondary education; Curriculum program; Multi-Tiered Support Systems (MTSS); Science of reading; Situational Leadership Theory